1991
DOI: 10.1159/000463206
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A: Interaction with Complement, Phagocytic Cells and Endothelial Cells

Abstract: Deposits of IgA together with complement (C) in different organs support the hypothesis that IgA can trigger inflammatory mechanisms. Some inflammatory mechanisms may be caused by activation of C and phagocytic cells. Therefore, it is essential to understand the interaction of IgA with C and phagocytic cells. Studies will be described demonstrating that polymeric human serum IgA is able to activate the alternative pathway of C and that the activating principle is located in the intact F(ab')2 portion of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Several studies have demonstrated that activation of the complement system augments the inflammatory cascade and potentiates tissue injury in IgAN (13). Roos et al (14) showed that those patients with IgAN with glomerular deposition of mannose-binding lectin (MBL) had more severe histologic damage and more proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that activation of the complement system augments the inflammatory cascade and potentiates tissue injury in IgAN (13). Roos et al (14) showed that those patients with IgAN with glomerular deposition of mannose-binding lectin (MBL) had more severe histologic damage and more proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…Complement activation by IgA has been previously shown to involve the alternative, but not the classical complement pathway (16,17). No data are available concerning the possible involvement of the lectin pathway.…”
mentioning
confidence: 99%
“…IgA does not have a C lq bhrdhig site, and therefore fads to fix complement by the classical pathway, but it now seems established that it can activate the alternative pathway in some circumstances , Bogers 1991, Valhn 1991. N-glycosylation of IgA has been shown to be important in C3 binding and production o f terminal complement components in a study employing IgA2 produced in the presence o f tunicamycin, which blocks the Asn-glycosylation pathway (Zhang 1994).…”
Section: 32mentioning
confidence: 99%